Intellectual property rights and agricultural development: Evidence from a worldwide index of IPRs in agriculture (1961-2018) - Mercedes Campi; Alessandro Nuvolari (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
This paper revises and updates the Campi-Nuvolari index of intellectual property protection for plant varieties (Campi and Nuvolari, 2015). The new index has been updated and provides yearly scores for the period 1961-2018 for a total number of 104 countries, which have legislation on plant variety protection in force. The new evidence highlights the tendency towards more similar and stronger systems of intellectual property rights (IPRs) worldwide, regardless of individual characteristics of countries. The signing of the TRIPS and of trade agreements with TRIPS-Plus provisions are major drivers of this process. In addition, certain features of countries such as the regulatory environment, the level of human capital, the importance of agricultural production, and openness to trade, are also significant determinants of the evolution of IPRs systems. We conclude discussing other possible applications of the data.
Keywords: Q01; O31; O34; O50; 330; Intellectual property rights; Plant breeders' rights; Patents; Agricultural development; International comparison